Dapatkah Brand Image, Social Media Marketing & Perceived Quality Terhadap Keputusan Pembelian Parfume HMNS di Sidoarjo - Ferry Irawan, Gusti Elang; Sari, Dewi Komala; Febriansah, Rizky Eka (Politeknik Piksi Ganesha Indonesia, 2025)
The purpose of this study is to examine the influence of Brand Image, Social Media Marketing, and Perceived Quality on purchasing decisions for HMNS Perfume in Sidoarjo. This type of research is based on a quantitative descriptive research approach. The population of this study was 96 consumers of HMNS perfume in Sidoarjo. The sampling technique was purposive sampling. The location of the study was in Sidoarjo. The data obtained will then be processed using the SmartPLS 4 program. The results of the study are that Brand Image, Social Media Marketing, and Perceived Quality have a significant positive effect on purchasing decisions for HMNS perfume in Sidoarjo